The Role of Memory Traces Quality in Directed Forgetting: A Comparison of Young and Older Participants. Issue 4 (23rd June 2014) - Collette, Fabienne; Grandjean, Julien; Lorant, Caroline; Bastin, Christine
A reduced directed-forgetting (DF) effect in normal aging has frequently been observed with the item method. These results were interpreted as age-related difficulties in inhibiting the processing of irrelevant information. However, since the performance of older adults is usually lower on items to remember, the age effect on DF abilities could also be interpreted as reflecting memory problems. Consequently, the present study aimed at investigating the influence of memory traces quality on the magnitude of the DF effects in normal aging. We predicted that increasing the quality of memory traces (by increasing presentation times at encoding) would be associated with attenuated DF effects in older participants due to the increased difficulty of inhibiting highly activated memory traces. A classical item-method DF paradigm was administered to 48 young and 48 older participants under short and long encoding conditions. Memory performance for information to memorize and to suppress was assessed with recall and recognition procedures, as well as with a Remember/Know/Guess (RKG) paradigm. The results indicated that, when memory traces are equated between groups, DF effects observed with the recall, recognition and RKG procedures are of similar amplitude in both groups (all ps>0.05). This suggests that the decreased DF effect previously observed in older adults might not actually depend on their inhibitory abilities but may rather reflect quantitative and qualitative differences in episodic memory functioning.